Exploring Factors Determining the Business Performance of Micro and Small Entreprises: Reality in Indonesian Muslim Entrepreneurs - La Ode Alimusa; Sitti Zakiah Ma'mun; Abdul Rahman; Ahmad Muhlis Nuryadi; Sahraman D. Hadji Latif (Universitas Muhammadiyah Yogyakarta, 2022)
Research aim: This paper aims to identify important influences on the company performance of Muslim business owners in Southeast Sulawesi, Indonesia, using a balanced scorecard development approach incorporating Islamic values and business practices.Design/Methodology/Approach: The research design used a quantitative approach called Exploratory Factor analysis through SPSS. The sampling technique was purposive sampling with 120 samples (Muslim entrepreneurs), with data collected through a survey questionnaire.Research findings: Three significant factors determining the business performance of Muslim entrepreneurs: strategy and internal business processes, business orientation, external stimuli, and Islamic business practices. Approaches to Islamic business practice are critical for improving Muslim entrepreneurs’ company performance.Theoretical contribution/ Originality: This finding is one of the new models of the balanced scorecard theory to measure and improve the performance of Indonesian Muslim entrepreneurs.Practitioner/Policy implication: Integration of business orientation with general approaches and sharia business practices such as halal product orientation and hard work can improve the business performance of Indonesian Muslim entrepreneurs.Research limitation/Implication: This study only investigated the performance of Muslim entrepreneurs in 7 districts/cities in Southeast Sulawesi with a sample of 120 Muslim MSMEs.